PEMANFAATAN PSEUDOMONAS AERUGINOSA UNTUK PENINGKATAN KUALITAS KOMPOS KERTAS DAN PENDEGRADASI LOGAM BERAT - Fitria, Anita Dwy; Yuliyani, Leny; Febryani, Noor; Alfath, Jusan Zaki; Sundawa, Rendi; Oktavia, Revina (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Improving the quality of compost paper is important to increase the availability of nutrients and reduce heavy metals. The quality of compost paper can be improved by using Pseudomonas aeruginosa bacteria, which can help mineralize nutrients and break down or convert heavy metals into less harmful forms. This study used a completely randomized design with five treatments in different concentrations of Pseudomonas aeruginosa bacteria (10%, 15%, 20%, and 25%). The analysis parameters used were pH H2O, Total N, organic C, C:N, Pb and Hg in the resulting compost. The results showed that the KK3 treatment produced higher pH H2O and Total N than other treatments. The availability of Pb metal on KK3 produced a relatively smaller value compared to other treatments, likewise, although it was not significantly different from C. The correlation results showed no significant relationship (p>0.05) between increasing doses of Pseudomonas aeruginosa and the availability of nutrients and heavy metals. The mineralization and incubation processes were factors in the study of improving the quality of compost by using Pseudomonas aeruginosa.